Return On Equity: Alokasi Dana Zakat, Profit Sharing Financing Dan Good Corporate Governance Pada Bank Umum Syariah Di Indonesia - Muhammad Aris Safii (Relevance: Journal of Management and Business, 2019)
There is a research gap the effect of zakat fund allocation profitability. Research (Romadhani & Wahyudi, 2015), Zakat Fund Allocation effect on ROE, in other hand (Romadhani & Wahyudi, 2015), zakat fund allocation there is not effect on ROE. Profitability represented by Return On Equity because it is an indicator of measurement of company performance to know the company's ability to generate profits with its own capital. In this study, researchers used a quantitative research approach. The sampling technique used by researchers was purposive sampling. The results of study is (1) The influence of Zakat Fund Allocation has a positive and significant effect on ROE (2) PSF has no effect on ROE. (3) GCG has a negative and significant effect on ROE.